2019
DOI: 10.1186/s40880-019-0368-6
|View full text |Cite
|
Sign up to set email alerts
|

Current cancer situation in China: good or bad news from the 2018 Global Cancer Statistics?

Abstract: Cancer is the leading cause of death in China and depicting the cancer pattern of China would provide basic knowhows on how to tackle it more effectively. In this study we have reviewed several reports of cancer burden, including the Global cancer statistics 2018 and Cancer statistics in China, 2015, along with the GLOBCAN 2018 online database, to investigate the differences of cancer patterns between China, the United States (USA) and the United Kingdom (UK). An estimated 4.3 million new cancer cases and 2.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
1,057
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,348 publications
(1,076 citation statements)
references
References 19 publications
12
1,057
2
5
Order By: Relevance
“…The current COVID-19 pandemic is particularly concerning, given the potential of spread from asymptomatic carriers (1-3). A report from China suggests that among those confirmed infected with SARS-CoV-2, approximately 1% of patients had cancer (3): 5-fold higher than the general incidence of cancer in China (201.7/100,000 persons) (7).…”
Section: Pre-existing Cancer and Cardiovascular Diseasementioning
confidence: 99%
“…The current COVID-19 pandemic is particularly concerning, given the potential of spread from asymptomatic carriers (1-3). A report from China suggests that among those confirmed infected with SARS-CoV-2, approximately 1% of patients had cancer (3): 5-fold higher than the general incidence of cancer in China (201.7/100,000 persons) (7).…”
Section: Pre-existing Cancer and Cardiovascular Diseasementioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most common malignancies, with high incidence and mortality rates, and ranks as the third most frequent cancer and the second leading cause of cancer‐related deaths worldwide . In China, CRC is the fifth most common cause of cancer‐related deaths (8.6%) . For patients with stage II‐III CRC, the standard, potentially curative treatment is radical resection and neoadjuvant chemoradiotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…1 In China, CRC is the fifth most common cause of cancer-related deaths (8.6%). 2 For patients with stage II-III CRC, the standard, potentially curative treatment is radical resection and neoadjuvant chemoradiotherapy. 3,4 Despite recent advances in chemotherapy, its clinical effect is not ideal, as indicated by local recurrence and distant metastasis rates.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest statistical data of GLOBOCAN in 2018, there were approximately 570 000 new cases of esophageal cancer and 500 000 deaths, ranking the eighth incidence and seventh of all the malignant carcinomas. In year 2018, there were approximately 307 000 new cases of esophageal cancer and 283 000 deaths in China, ranking fifth in the incidence of malignant tumors and fourth in the mortality rate . As is already known, the development of esophageal cancer is the result of the interaction of genes and environmental factors, but the specific pathogenesis of both have not as yet been fully elucidated, and need further exploration .…”
Section: Introductionmentioning
confidence: 99%
“…In year 2018, there were approximately 307 000 new cases of esophageal cancer and 283 000 deaths in China, ranking fifth in the incidence of malignant tumors and fourth in the mortality rate. 2 As is already known, the development of esophageal cancer is the result of the interaction of genes and environmental factors, but the specific pathogenesis of both have not as yet been fully elucidated, and need further exploration. 3 In recent years, studies have confirmed that gene single nucleotide polymorphism (SNP) was closely correlated with the cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%